Social Media Marketings Effect on Event-Based Tourism Development in Pagar Alam - Hasan, Hanif; Syahputra, Muhammad Halfi Indra; Karo, Pelliyezer Karo; Permatasari , Mustika; Khadijah, Khadijah (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study investigates the influence of social media marketing on the development of event-based tourism in Pagar Alam, a growing tourism destination in Indonesia known for its cultural festivals and natural attractions. Utilizing a quantitative approach, data were collected through a structured questionnaire distributed to 100 tourists who had participated in local tourism events. The research focused on four key dimensions of social media marketing: platform exposure, content engagement, message credibility, and interactivity. Descriptive statistics, classical assumption tests, and multiple linear regression were employed to analyze the data using SPSS version 26. The results showed that social media marketing significantly affects event-based tourism development, with content engagement and message credibility emerging as the most influential factors. The instruments used were confirmed to be both valid and reliable. Furthermore, no significant differences were found across gender or age groups, indicating that the influence of social media is consistent among various demographic segments. The findings highlight the importance of creating engaging and credible digital content to attract tourists and enhance destination visibility. This study offers practical insights for tourism stakeholders to improve promotional strategies through social media and suggests further research to explore additional variables such as visitor satisfaction and digital behavior trends